Effect of SY009, a novel SGLT1 inhibitor, on the plasma metabolome and bile acids in patients with type 2 diabetes mellitus - Haoyi Yang; Yuwen Zhang; Yuxin Hong; Yuan Wei; Yuning Zhu; Lei Huang; Yuanxun Yang; Runbin Sun; Runbin Sun; Runbin Sun; Juan Li; Juan Li; et al. (Frontiers in Endocrinology, 2025)
ContextAs a novel SGLT1 inhibitor, SY-009 has been preliminarily confirmed in a phase Ib clinical study for its ability to reduce postprandial blood glucose in patients with type 2 diabetes mellitus (T2DM). However, the effects of SY-009 on human plasma metabolomics are still unknown.ObjectiveThis study aimed to explore the effects of SY-009 on plasma metabolomics in patients with T2DM and the potential metabolic regulatory mechanism involved.Study designIn the phase Ib study, a total of 50 participants with T2DM were enrolled and randomly assigned to the 0.5 mg BID, 1 mg BID, 2 mg BID, 1 mg QD, and 2 mg QD dose groups, with a 4:1 random allocation within each group to receive either the SY-009 capsule or placebo. We conducted untargeted and targeted metabolomics analyses on plasma samples from the phase Ib clinical study.ResultsUntargeted metabolomics revealed that, after SY009 treatment, there were differences in metabolic pathways, including primary bile acid biosynthesis; biosynthesis of unsaturated fatty acid; steroid hormone biosynthesis; purine metabolism; phenylalanine, tyrosine and tryptophan biosynthesis. In particular, the increase in bile acid-related metabolites in the 2 mg BID group was significantly greater than that in the placebo group, and unsaturated fatty acid-related metabolites decreased in both the 2 mg BID group and the placebo group, but there was no significant difference between the two groups. After comprehensive consideration, bile acids were taken as our target for accurate quantification via targeted metabolomics. Compared with those in the placebo group, the levels of several bile acids were significantly greater in the SY-009-treated groups. Moreover, the proportion of free bile acids decreased significantly, the proportion of glycine-conjugated bile acids increased significantly, the proportion of taurine-conjugated bile acids tended to be stable, and PBA/SBA significantly increased after SY-009 administration.ConclusionsSY-009 caused a series of postprandial plasma metabolite changes in patients with T2DM, especially significant changes in the bile acid profile, which provides a new perspective on the mechanism by which SY-009 lowers blood glucose.Clinical trial registrationhttps://www.clinicaltrials.gov, identifier NCT04345107.